PENINGKATAN KETERAMPILAN MENYIMAK DONGENG DENGAN MEDIA FILM SISWA KELAS V SD NEGERI WONOLELO 1 SAWANGAN MAGELANG - Tuti Tri Setiawati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2014)
This study aims to (1) describe the increase in activity in the learning of students listened to the media fairy tale movies Elementary School fifth grade students Wonolelo 1 Sawangan, Magelang and (2) describe an increase listening skills with the media fairy tale movies Elementary School fifth grade students Wonolelo 1 Sawangan, Magelang.This reseach is a classroom action reseach. The subject were all students of class V, amounting to 20 students. Data obtained during the learning process in the classroom by using the medium of film. Actions carried out in two cycles . The instrument used is the student activity sheets and teacher observation , intervie, test, and documentation. The data were analyzed by descriptive qualitative is based on the reflection of each cycle the action.Results of this study indicate that (1) the medium of film can improve the learning activity of students in the fifth grade students listening to a fairy tale Wonolelo state primary Wonolelo 1, Sawangan, Magelang. (2) the medium of film can improve listening skills fairytale Elementary School fifth grade students primary Wonolelo 1, Sawangan, Magelang.